Dectin-3 Recognizes Glucuronoxylomannan of Cryptococcus neoformans Serotype AD and Cryptococcus gattii Serotype B to Initiate Host Defense Against Cryptococcosis - Hua-Rong Huang (Frontiers in Immunology, 2018)
Cryptococcus neoformans and Cryptococcus gattii cause life-threatening meningoencephalitis or lung diseases in immunocompetent individuals or immunocompromised ones. C. neoformans and C. gattii are subdivided into five serotypes based on their capsular glucuronoxylomannan (GXM). C. neoformans consists of serotypes A, D, and AD hybrid, and C. gattii consists of serotypes B and C. Given structural differences of GXM between C. neoformans and C. gattii, it remains unclear that how innate immune system recognizes GXM. Here, we report that C-type lectin receptor Dectin-3 (MCL encoded by Clec4d) is a direct receptor for GXMs from C. neoformans serotype AD (C.n-AD) and C. gattii serotype B (C.g-B). GXMs from C.n-AD and C.g-B activated NF-κB and ERK pathways to induce pro-inflammatory cytokine production, whereas it was completely abolished due to deficiency of Dectin-3 or caspase recruitment domain family member 9 (CARD9). Upon pulmonary C.n-AD and C.g-B infection, Dectin-3- and CARD9-deficient mice were highly susceptible and showed augmented lung injury due to impairment of alveolar macrophage accumulation and killing activities. Our study provides the first biological and genetic evidence demonstrating that Dectin-3 recognizes GXM of C.n-AD and C.g-B to initiate host defense against cryptococcosis.